Revisión estadística de diferentes índices en el recién nacido con peso superior a 2,500 gramos. - Sosa Bens, D.; Peña Machado, M.; Torres de la Luz, A.; Mir Páez, M.; Suárez, Esther; Royo, Irma; Arana, Mirem; Brizuela, G. (Revista Cubana de Pediatría, 2023)
Revisión estadística